Methylation profiling in oral squamous cell carcinoma / Khor Goot Heah - Khor, Goot Heah (2014)

(untitled)
ntroduction: DNA methylation is an epigenetic phenomenon at molecular level that involves gene expression regulation of cell development and differentiation, and diseases. DNA hypermethylation in a gene promoter region shows dramatic effects on gene expression and is a common phenomenon in initiation and progression of many solid tumours that includes Oral Squamous Cell Carcinoma (OSCC). Silencing of hypermethylated genes in promoter regions is a frequent phenomenon in different types of cancer and has achieved increasing diagnostic and therapeutic importance since the changes are reversible. Thus, methylation analysis may provide promising clinical applications that include the development of biomarkers, assessment of prognosis and prediction of the therapeutic response in oral malignancy. For years, OSCC has been amongst the leading cancers in developing countries. Despite considerable efforts in research studies and cancer treatments, a 5-year survival rate for OSCC has not shown any significant improvement. To improve on this situation, it is therefore necessary to understand the fundamental biological processes and to identify appropriate prognostic factors of OSCC on DNA hypermethylation-mediated silencing that leads to cancer progression. Objectives: OSCC methylation profiling was investigated by microarray analysis followed by identification and verification of significantly hypermethylated genes and their protein products. To achieve this, methylation specific polymerase chain reaction (MSPCR) and immunohistochemical (IHC) analysis were used. Both analyses were conducted on selected promoter hypermethylation markers used for detecting the epigenetic alterations associated with OSCC. In this study, the significant pathways of selected hypermethylated genes that are involved in oral carcinogenesis were also elucidated. Finally, relations of demographic and iv clinicopathological characteristics along with these signature genes were conducted for prognostic purposes of OSCC. Materials and methods: Genome-wide analysis of 4 normal oral mucosa and 20 OSCC tissues were conducted using Illumina methylation microarray. The specified differential genes were selected from a gene list and their methylation statuses and protein expressions were further verified by an independent cohort sample of 40 OSCC samples. Lastly, statistical analysis conducted on demographic, clinicopathological data and gene hypermethylations for OSCC prognostication. Results: Unsupervised hierarchical clustering of methylation data revealed distinct methylation patterns between the normal and the tumour tissues. For tumour tissues, high frequencies of promoter hypermethylation were found in p16, DDAH2, DUSP1, PIKCR3, TP73, MEF2D, RRM2 and CELSR3 genes in the MSPCR analysis; whereas low positive immunostaining of DDAH2, DUSP1, MEF2D and RRM2 were demonstrated in the IHC analysis. Notably, an inverse correlation was observed between hypermethylations and protein expressions of DDAH2, DUSP1, MEF2D and RRM2. In addition to that, significant association was found between p16 and TP73 hypermethylation with patients’ tumour site, and CELSR3 and TP73 hypermethylation with patients’ invasive stages. Furthermore, DDAH2 and CELSR3 hypermethylation, and RRM2 expression were correlated significantly with patients’ age. Finally, gender showed a significant difference in the survival rate with 24.2% for males and 46.5% for females. v Conclusions: Multiple candidate genes were identified using computational and gene-specific validation approaches in this study. The results provide a new insight into the molecular basis of promoter hypermethylation and prognostic values of OSCC. Nevertheless, the identified candidate genes revealed from the present research are worth making further investigations on oral carcinogenesis.